Urbanization and translocation disrupt the relationship between host density and parasite abundance. Issue 4 (20th February 2020) - DeVore, Jayna L.; Shine, Richard; Ducatez, Simon
Abstract: The species interactions that structure natural communities are increasingly disrupted by radical habitat change resulting from the widespread processes of urbanization and species translocations. Although many species are disadvantaged by these changes, others thrive in these new environments, achieving densities that exceed those in natural habitats. Often the same species that benefit from urbanization are successful invaders in introduced habitats, suggesting that similar processes promote these species in both environments. Both processes may especially benefit certain species by modifying their interactions with harmful parasites ('enemy release'). To detect such modifications, we first need to identify the mechanisms underlying host–parasite associations in natural populations, then test whether they are disrupted in cities and introduced habitats. We studied the interaction between the cane toad Rhinella marina, a globally invasive species native to South America, and its Amblyomma ticks. Our field study of 642 cane toads across 46 sites within their native range in French Guiana revealed that 56% of toads carried ticks, and that toads with ticks were in poor body condition relative to uninfected conspecifics. Across natural and disturbed habitats tick prevalence and abundance increased with toad density, but this association was disrupted in the urban environment, where tick abundance remained low even where toad densities were high, and prevalence decreased with density. Reductions in the abundance of ticks in urban habitats may be attributable to pesticides (which are sprayed for mosquito control but are also lethal to ticks), and our literature review shows that tick abundance is generally lower in cane toads from urban habitats across South America. In the invasive range, ticks were either absent (in 1, 960 toads from Puerto Rico, Hawai'i, Japan and Australia) or less abundant (in Florida and the Caribbean; literature review). The positive relationship between host density and parasite abundance is thought to be a key mechanism through which parasites regulate host populations; anthropogenic processes that disrupt this relationship may allow populations in urban and introduced habitats to persist at densities that would otherwise lead to severe impacts from parasites. Abstract : Within native habitats, cane toad density and tick abundance are positively related, such that toads living at higher densities suffer from increased parasitism. This density‐dependent relationship is disrupted by both urbanization and translocation, allowing urban and invasive toad populations to achieve high densities without incurring substantial parasite burdens.